Reflection of Polarized Light at Quasi-Index-Matched Dielectric-Conductor Interfaces - R. M. A. Azzam (Jordan Journal of Physics, 2025)
Quasi-index-matched (QIM) dielectric-conductor interfaces are characterized by a unit-magnitude complex relative dielectric function, ε= exp(- jθ ),0 ≤ θ ≤ π, and exhibit minimum reflectance at normal incidence. Their reflection properties are analyzed in detail as functions of the incident linear polarization (p or s), angle of incidence ϕ and θ. Complex-plane trajectories of the Fresnel reflection coefficients rp(ϕ), rs(ϕ) and their ratio p(ϕ)= rp /rs= tanΨ exp(jΔ) as ϕ increases from 0 to 90° are presented at discrete values of θ, Absolute values and phase angles of rp, rs and p are also plotted as functions of ϕ, Finally, the pseudo-Brewster angle of minimum |rp|, the second-Brewster angle of minimum |p|, the principal angle at which Δ= π / 2 , and the special angle (ϕ= sin-1 √ 0.5secθ) at which δp = arg(rp) = ±πof QIM interfaces are determined as functions of θ. Keywords: Physical optics; Reflection; Interfaces; Polarization; Dielectric function; Ellipsometry. PACS: 42. Optics.